Diseño de la automatización de las estaciones de bombeo y tanques de reserva del sistema de agua potable de la ciudad de Loja. - Mejía Torres, Santiago Mauricio (2011)
The system automation is applied to the 22 stations of pumping with its respective unit’s reservation that it counts at the moment in operation the (UMAPAL). To elaborate efficiently the phases of design the system, it has been continued as model reference the pyramid CIM (Fig.14) of automation of systems where in order to have an advance organized and sequential, are approached the aspects design and specifications of the teams and facilities that you/they conformed one each of the levels the system instrumentation and control, the algorithm of the control system is developed that allows to carry out the works of Reading, visualization and control of all the variables that intervene in the process and the respective storage (pressure, flow, level, residual clarification, state of the teams, alarms). Attaching to international standards for the elaboration of the necessary bid sheets for the execution of this project in the future. Finally he/she is carried out the economic and environmental evaluation where is analysed the I mount of investment that generates the setting in march of the project, as well as the time of recovery of the investment and the positive impact on the environment. For economic situations and of character office worker, it exists the inconvenience that the project is not started. For he/she is carried out it a simulation of the whole system, as well as the mediating demonstration a prototype that has been designed and built for the effect, that it provides the capacity to verify the advantages and utilities taking a census of the variables that intervene, processing them and showing them in real time by means of the software Lab VIEW. It is important to conclude that the proposed automation system, it will allow when having (UMAPAL) a tool that saved him/her inconveniences in the technical and commercial field, since they were avoided you overflow in the distribution tanks and it improved the control quality in what concerns to the distribution volumes as well as the consumption of energy of the teams of pumping will be minimized.